2015
DOI: 10.1007/s10157-015-1097-z
|View full text |Cite
|
Sign up to set email alerts
|

Hypomagnesemia and atherogenic dyslipidemia in chronic kidney disease: surrogate markers for increased cardiovascular risk

Abstract: Our results suggest a strong association of hypomagnesemia and atherogenic dyslipidemia in patients with CKD. This gains particular importance in the high cardiovascular risk-borne CKD patients, as supplementing magnesium would go a long way in reducing the risk of cardiovascular morbidity and mortality in CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…Hypomagnesemia is a recognized risk for cardiac rhythm disturbances and is associated with a higher risk for cardiovascular events (3). There is also growing evidence supporting an association between lower serum magnesium levels and dyslipidemia, metabolic syndrome, endothelial dysfunction, atherosclerosis, and vascular calcification, all of which could potentially be mechanisms to explain the observations in our study (1519). Second, infection is an ongoing threat to the successful execution of PD.…”
Section: Discussionsupporting
confidence: 54%
“…Hypomagnesemia is a recognized risk for cardiac rhythm disturbances and is associated with a higher risk for cardiovascular events (3). There is also growing evidence supporting an association between lower serum magnesium levels and dyslipidemia, metabolic syndrome, endothelial dysfunction, atherosclerosis, and vascular calcification, all of which could potentially be mechanisms to explain the observations in our study (1519). Second, infection is an ongoing threat to the successful execution of PD.…”
Section: Discussionsupporting
confidence: 54%
“…One animal study [29] postulated a favorable effect of magnesium on lipid metabolism in the conversion of triglycerides to high-density lipoprotein (HDL) cholesterol. This relationship is supported by epidemiological studies [30][31][32] in which the serum magnesium level was inversely associated with total, low-density lipoprotein, and non-HDL cholesterol and positively associated with HDL cholesterol. One of the mechanisms by which magnesium lowers blood pressure is by acting as a natural calcium channel blocker.…”
Section: Discussionsupporting
confidence: 50%
“…[26][27][28] It has been reported that atherogenic dyslipidemia and systemic inflammation are symptoms commonly seen in patients with CKD due to metabolic disturbances and the accumulation of vasotoxic substances. [29][30][31] In addition, ongoing endothelial damage in the capillary system of the renal medulla with vascular rarefaction is unfavorably associated with developing CKD. 32 On the other hand, evidence suggests that regular exercise confers cardiometabolic benefits and structural and functional adaptations of the endothelial response to vasoconstrictors.…”
Section: Principal Findingsmentioning
confidence: 99%